Simultaneous removal of nutrients and endocrine disrupting chemicals by aerobic granular sludge and advanced oxidation processes - Martínez Castellanos, Reynel (2020)
This research work aimed to evaluate the removal of organic matter, nutrients and endocrine disrupting chemicals (EDCs), particularly 17β-estradiol (E2) and 17αethinylestradiol (EE2), from synthetic aqueous matrices, using aerobic granular sludge (AGS) and heterogeneous photocatalysis in a membrane micro-reactor with continuous H2O2 permeation. The experimental work was separated into three stages. In the first, the effect of solids retention time (SRT) on the stability and performance of an AGS reactor over 392 days was evaluated. Higher COD, ammonia and total phosphorus removal efficiencies (above 93%) were observed at an SRT of 15 days. In the second stage, the performance of the reactor was monitored for 151 days, both in terms of COD, NH4 + , and PO4 3- removal, and DE abatement, while the estrogenic activity was assessed in the effluent. The results showed that the system was able to achieve high removals of COD (93%), NH4 + (87%) and PO4 3- (87%), with a EDCs biodegradation percentage above 90%, while moderate levels of estrogenic activity were detected in the reactor effluent samples (0.122 µg L-1 EQ-E2). Finally, in the third stage, the removal of EDCs was investigated by heterogeneous photocatalysis in the membrane micro reactor. The UVC/H2O2/TiO2 system was the one that showed the highest oxidation capacity of EDCs, with a removal of around 50% for the synthetic matrix evaluated.